Realizing Merdeka Belajar: Case Study of MBKM Teaching Assistance Program at the Family Course Pare - Jannah, Della Maulatul; Islam, Raudhatul; Lestari, Wahyu; Aziz, Abd (BABASAL English Education Journal, 2024)
This study aims to determine the application of the MBKM Teaching Assistance program in institutions as an effort to realize independent learning. So far, students and teachers have been teaching and learning to get high scores in exams so that learning is monotonous and does not hone students' skills at the primary, secondary and tertiary education levels. As a result, the quality of graduates does not have the competencies needed by the world of work. The government is trying to overcome this problem through the Merdeka Belajar policy. One of the Merdeka Belajar programs for students is Teaching Assistance by involving students to help institutions carry out fun teaching and learning activities. This case study research was conducted at one of the institutions in Pare through observation, interviews and document analysis. The results showed that the MBKM Teaching Assistance program by sending students as agents of change to institutions has helped the implementation of teaching and learning activities. Students, teachers and students are very enthusiastic despite facing various challenges. Students hope that there will be sustainable changes in teaching and learning activities after the MBKM Teaching Assistance program ends.